Antimicrobial Activity Test of Alkaloid Rich Extract from Morinda citrifolia Leaves Against the Growth of Pathogenic Bacteria Staphylococcus aureus and Escherichia coli - Josafat Alexander, Irving; Surbakti, Mariana; Sirait, Gloria; Silaban, Ramlan (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2026)
This study aims to analyze the antimicrobial activity of alkaloid compounds from noni leaf extract (Morinda citrifolia) against the growth of pathogenic bacteria Staphylococcus aureus and Escherichia coli. The study applied a quantitative experimental laboratory approach. Extraction was carried out using the maceration method with 96% ethanol, followed by qualitative phytochemical analysis using Mayer, Dragendorff, and Wagner reagents to identify the presence of alkaloids. Using the Kirby-Bauer disk diffusion method, the antibacterial efficacy was evaluated at concentrations of 25%, 50%, 75%, and 100%. The primary indicator utilized was the size of the regions where bacteria could not thrive. Basic statistics and ANOVA analyses were utilized for data assessment. About 10.45% of alkaloids were found in the results. As the extract concentration grew, the quantity of bacterial development arrested did as well. The most notable impact was observed at the 100% concentration, with no growth zones of 18.9 mm for S. aureus and 15.8 mm for E. coli. The extract was more effective against Gram-positive bacteria. With p values less than 0.05, the statistical analysis found significant variations among the various treatments. Finally, the alkaloids found in noni leaves have a lot of potential to work as natural antibacterial agents and could be a substitute to fight antibiotic resistance.